Estimating the Frequency of a Storm Event: How to Use NOAA Atlas 14 Point Precipitation Frequency Estimates: AE587/AE587, 5/2023 - Her, Young Gu; Bean, Eban; Martinez, Christopher (EDIS, 2023)
This article introduces NOAA Atlas 14 and explains how to use it to help Extension agents and the general public estimate the frequency of any storm event of interest. The frequency estimate of a storm event using NOAA Atlas 14 helps the user to understand how large a storm is in relation to the historical storm events that occurred at a certain location. In addition, the information on the estimate’s confidence interval provided by NOAA Atlas 14 is expected to help people better understand the probabilistic nature of rainfall events. Written by Young Gu Her, Eban Bean, and Christopher Martinez, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2023.